Daratumumab prevents programmed death ligand‐1 expression on antigen‐presenting cells in de novo multiple myeloma. (28th January 2020) - Stocker, Nicolas; Gaugler, Béatrice; Ricard, Laure; de Vassoigne, Frédéric; Marjanovic, Zora; Mohty, Mohamad; Malard, Florent
Abstract: Background: Daratumumab (Dara), an anti‐CD38 monoclonal antibody, has an immunologic mechanism of action through targeting of CD38 expressing immune cells in patients with multiple myeloma (MM). Furthermore, it was recently shown that CD38 upregulation in tumors, is a major mechanism of acquired resistance to antiprogrammed cell death 1 (PD‐1)/programmed cell death ligand 1 (PD‐L1). Therefore, we decided to evaluate the immunomodulatory effects of CD38 blockade by Dara on the PD‐L1 expressing immune cells. Methods: We analyzed CD38 and PD‐L1 expression on immune cells at different time points in 18 newly diagnosed MM receiving bortezomib, lenalidomide and dexamethasone, with or without Dara. Results: We first confirmed that CD38 is widely expressed on immune cells, with the strongest expression on plasmacytoid dendritic cells (pDC). Furthermore, Dara induces a strong depletion of pDC in addition to the well‐known rapid depletion of natural killer cells. Finally, we found that PD‐L1 expression on antigen‐presenting cells (APC) increases with MM treatment in patients that did not received Dara, while addition of Dara prevents this increase. Conclusion: Overall, our results suggest new mechanisms of action of Dara through depletion of pDC and prevention of PD‐L1 upregulation expression on APC. Our finding provides new evidences for development of therapeutic strategies targeting both CD38 and PD‐L1/PD‐1 pathway in patients with MM. Abstract : Daratumumab have immunomodulatory effects on CD38‐expressing immune cells. Daratumumab prevents PDL1 expression on CD38‐expressing antigen‐presenting cells.